2021
DOI: 10.21203/rs.3.rs-154335/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Gut Microbiota is Associated with the Small Intestinal Paracellular Permeability and the Development of the Immune System in Healthy Children During the First Two Years of Life

Abstract: BackgroundThe intestinal barrier plays an important role in the defense against infections, and nutritional, endocrine, and immune functions. The gut microbiota playing important role in development of the gastrointestinal tract can impact intestinal permeability and immunity during early life, but data concerning this problem are scare.MethodsWe analyzed the microbiota in fecal samples (101 samples in total) collected longitudinally over 24 months from 21 newborns to investigate whether the markers of small i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The first two years are thought to be crucial for the development of the symbiotic microbiome on mucosal surfaces that is relevant in the maintenance of health and development of disease 17 . Microbial diversity in the neonatal gut is influenced by breast or formula feeding but early differences are lost at one year of age 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The first two years are thought to be crucial for the development of the symbiotic microbiome on mucosal surfaces that is relevant in the maintenance of health and development of disease 17 . Microbial diversity in the neonatal gut is influenced by breast or formula feeding but early differences are lost at one year of age 18 .…”
Section: Discussionmentioning
confidence: 99%
“…[66,67] The complex interplays between the developing microbiome and the host at the intestinal mucosa profoundly impact the development of the immune system and long-term health, especially during the critical time window of the perinatal period. [68] Studies have found that fecal calprotectin regulates the intestinal microbiota and immune system development in neonates. [69,70] In this study, we found that Enterococcus, a genus reported to be associated with active inflammation among IBD patients, [71,72] was positively correlated with calprotectin levels and the intensities of four sphingolipids.…”
Section: Discussionmentioning
confidence: 99%